Better, Faster, Stronger: The Evolution of Co-authorship in International Management Research Between 1990 and 2016. (November 2021) - Wieczorek, Oliver; Eckl, Markus; Bausch, Madeleine; Radisch, Erik; Barmeyer, Christoph; Rehbein, Malte
As a border-transcending discipline, the advancement of international management research depends on collaboration between scholars, universities, and nations to account for the diversity and complexity of management phenomena. Yet, relatively little is known about how international management has evolved as a field of research. We address this gap by examining the evolution of collaboration patterns on three levels of analysis, applying the concepts of cumulative advantage, preferential attachment, and isomorphic behavior in a diachronic network analysis. Based on 6, 874 articles published between 1990 and 2016 in eight international management journals, our analysis shows that collaboration is driven by a few key players on each level. Although the US and UK still represent hubs, semi-peripheral actors from Europe and Asia enter the landscape. Nevertheless, non-western actors are still underrepresented. We tie this effect to the expertise-based hegemonic status of American and British business schools and dynamics of cumulative advantage on country-level.